ANALISIS PROSEDUR DAN PERLAKUAN AKUNTANSI PENJUALAN SUKUK RITEL DENGAN AKAD IJARAH ASSET TO BE LEASED PADA BANK SYARIAH MANDIRI - Dwi Saputri, Retno; Nasution, Hafifah (Sekolah Tinggi Ilmu Ekonomi Totalwin, 2021)
This research was conducted in one of the retail state sukuk distribution partners, namely Bank Syariah Mandiri (BSM) with the aim of knowing how the sales procedure and accounting treatment for the sale of retail type state sukuk issued by the government. The research method used in this research is descriptive qualitative analysis method, and this research uses technical analysis of case studies. The results obtained in this study are that Bank Syariah Mandiri as a sales distribution partner in carrying out sales procedures, there is one provision that is not in accordance with the State Retail Sukuk Information Memorandum, namely the provisions for securities account storage fees. Meanwhile, the accounting treatment for the sale of Sukuk Ijarah at Bank Syariah Mandiri is in accordance with PSAK Sharia 110 concerning Sukuk Accounting with disclosure of the explanation of the underlying assets by the Minister of Finance, not Bank Syariah Mandiri.